Animal assisted therapy : use application by condition - Altschuler, Eric Lewin (Oxford University Press, 2023)
Animal Assisted Therapy Use Application by Condition provides the most updated and comprehensive data knowledge on animal-assisted therapy. The book synthesizes historical information, theory, clinical practice, and data from recent clinical studies on animal-assisted therapy for post-traumatic stress disorder (PTSD) and other diseases. Written by international experts drawn from the fields of medicine, clinical psychology and therapy, speech therapy, clinical research, and animal training and welfare, this book employs a hypothesis driven, data rich approach to inform readers on current research and serve as a reference for clinical practice and use of animal-assisted therapy.